Rancang Bangun Aplikasi Proses Pembuahan Sel Telur dengan Virtual Reality 3D Berbasis Android - Gustina, Dian; Chandra, Yudi Irawan; Setiawan, Rino Yulendri (Lembaga Riset dan Pengabdian Masyarakat Institut Bisnis Nusantara, 2025)
Technological development in the field of reproductive medicine continues to grow rapidly, including in the process of egg fertilization. One promising approach is the use of 3D Virtual Reality (VR) technology to visualize this process interactively. This research aims to design and build an Android-based application that uses 3D VR technology to realistically visualize the process of egg fertilization. The development method used is the agile model, which allows developers to adapt to changes and user feedback efficiently. The development team engaged in an iterative development cycle, which included planning, analysis, design, implementation and testing. This model allows the app to evolve iteratively, with a focus on providing added value to users at each iteration. The resulting application utilizes 3D VR technology to create an immersive visual experience for users. They can see firsthand the process of fertilizing an egg on a microscopic scale, with details that include the interaction between the sperm cell and the egg. Additional features such as interactive controls and audio narration provide users with a thorough and engaging learning experience. Initial testing results show that this app has great potential in supporting education and understanding of the human reproductive process. User response to the 3D VR experience was very positive, with many users finding it a useful and engaging tool. Further development and feature enhancements can be made based on feedback from users, so that the app can continue to grow and increase its impact in the field of reproductive medicine.